Pre-treatment of surface waters for ceramic microfiltration - Metcalfe, D.; Jarvis, Peter; Rockey, C.; Judd, Simon J. (Cranfield University, 2016)
The influence of pre-treatment on the suppression of irreversible (IR) fouling of ceramic membranes challenged with three UK surface waters has been studied at pilot scale. An initial scoping study compared the efficacy of suspended ion exchange (SIX) and clarification (coagulation followed by sludge blanket clarification) individually and in combination. Direct membrane filtration following in-line coagulation (ILCA) was also investigated with and without SIX. The impact on the various organic fractions, specifically high molecular weight (HMW) biopolymers (BPs) and humic substances (HSs), and lower molecular weight (LMW) building blocks (BBs) and neutrals, was studied using liquid chromatography-organic carbon detection (LC-OCD). Results revealed SIX and coagulation to preferentially remove the LMW and HMW organic fractions respectively. Residual HMW organic matter (primarily BPs) following SIX pre-treatment were retained by the membrane which led to rapid irreversible fouling. Coagulation pre-treatment provided stable membrane operation and the residual LMW organics were not significantly retained by the membrane. Combining clarification and SIX resulted in significantly increased removal of organics and lower membrane fouling rates. Tests performed using SIX and ILCA revealed high dissolved organic carbon (DOC) removal compared to SIX with clarification. However, unlike the case for clarification with SIX, the addition of SIX to optimised ILCA dosing offered no additional suppression of membrane fouling compared to ILCA alone. Optimised ILCA pretreatment led to very low IR fouling rates of <0.3 kPa/day trans-membrane pressure, despite highly challenging operating conditions of elevated fluxes (185 L m−2 h−1) and highly variable feedwater dissolved organic carbon concentrations.
Keywords: Ceramic membrane; Pretreatment; Ion exchange; Coagulation; Organic fouling